2020
DOI: 10.5194/gchron-2020-14
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calibrating a long-term meteoric <sup>10</sup>Be delivery rate into Western US glacial deposits through a comparison of complimentary meteoric and in situ-produced <sup>10</sup>Be depth profiles

Abstract: Abstract. Meteoric 10Be (10Bemet) concentrations in soil profiles great potential as a geochronometer and a tracer of Earth surface processes, particularly in fine-grained soils lacking quartz that would preclude the use of in situ-produced 10Be (10Bein situ). One prerequisite for using this technique for accurately calculating rates and dates is constraining the delivery, or flux, of 10Bemet to a site. However, few studies to date have quantified long-term (i.e. millennial) delivery rates. In this study, we c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Line 34: Also Al-OOH (e.g. Graly et al, 2010) Line 43: I might avoid implying that most previous work is flawed here. These issues have been discussed and debated since the inception of the method with the work of Pavich and Monaghan.…”
Section: Interactive Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Line 34: Also Al-OOH (e.g. Graly et al, 2010) Line 43: I might avoid implying that most previous work is flawed here. These issues have been discussed and debated since the inception of the method with the work of Pavich and Monaghan.…”
Section: Interactive Commentmentioning
confidence: 99%
“…The paper should flow naturally without the need to do this. Line 293: Graly et al 2010 tested this claim and found that grain size effects could explain subsurface maxima in none of the 29 soil profiles analyzed. A far better explanation is that 10Be is incorporated into the lattices of newly forming clays and oxyhydroxides at depth (e.g.…”
Section: Interactive Commentmentioning
confidence: 99%
“…Revised to "target nuclei" Line 34: Also Al-OOH (e.g. Graly et al, 2010 ) Revised to "Fe-and Al-oxyhydroxides", citation added Line 43: I might avoid implying that most previous work is flawed here. These issues have been discussed and debated since the inception of the method with the work of C4 Pavich and Monaghan.…”
Section: Sincerelymentioning
confidence: 99%
“…After re-organization of sections as advised by both reviewers, we have greatly reduced section callouts throughout the manuscript. Line 293: Graly et al 2010 tested this claim and found that grain size effects could C8 explain subsurface maxima in none of the 29 soil profiles analyzed. A far better explanation is that 10Be is incorporated into the lattices of newly forming clays and oxyhydroxides at depth (e.g.…”
Section: Lines 269 and 276 / Tablementioning
confidence: 99%